Feedlot growth performance and carcass characteristics of steers backgrounded on buffel grass or buffel–Desmanthus mixed pastures - Mwangi, Felista Waithira; Savage, Darryl; Gardiner, Christopher Peter; Charmley, Edward; Malau-Aduli, Bunmi Sherifat; Kinobe, Robert Tumwesigye; Malau-Aduli, Aduli Enoch Othniel (Frontiers in Veterinary Science, 2022)
Feedlot performance and carcass characteristics of tropical beef steers backgrounded on buffel grass (Cenchrus ciliaris) only or buffel grass oversown with desmanthus (Desmanthus spp.; 11.5% initial sward dry matter) were evaluated. It was hypothesised that tropical beef cattle steers backgrounded on buffel grass only or buffel grass oversown with desmanthus with similar backgrounding growth performance will not differ in feedlot growth performance and carcass quality. Three hundred and twelve Bos indicus x Bos taurus tropical composite steers, 20 - 23 months old and weighing 413 ± 24 kg, previously backgrounded on buffel grass only or buffel-desmanthus mixed pastures for 147 days were finished on a concentrate diet in the feedlot for 110 days before slaughter. Buffel-desmanthus backgrounded steers had slightly higher average daily gain (ADG; 1.8 kg/day; p = 0.01) and residual feed intake (RFI; 0.1 kg/day) than the buffel grass backgrounded steers that had 1.7 kg/day ADG and -0.1 kg/day RFI (p = 0.04). However, final liveweight and dry matter intake were not different (p ≥ 0.59). All the carcass traits measured were not different (p ≥ 0.06). Only 4% buffel grass and 8% buffel-desmanthus backgrounded steers fell short of the Meat Standards Australia (MSA) index, a level that is within the 4 - 9% reported for cattle produced in Queensland and slaughtered between July 2019 and June 2020. These findings indicate that desmanthus can be used to background beef cattle in northern Australia vertosol soil regions, where there is a paucity of adapted pasture legumes, with no negative impact on feedlot performance and carcass quality. The hypothesis that tropical beef cattle steers backgrounded on buffel grass only pastures or buffel grass oversown with desmanthus with similar backgrounding growth performance will have similar feedlot growth performance and carcass quality was accepted.